Research on the relationship of institutional innovation, organizational learning and synergistic effect: An empirical study of chineses university spin-offs - Hao Zhang; Ding Yunlong (Journal of Industrial Engineering and Management (JIEM), 2014)
Purpose: At present, the Central Government of China pays more attention to the synergistic innovation, and the national strategy policy of "innovation driven development" are made to implementations. Thus, the university plays an important role in the national innovation system, so that how the university gets involved in innovative activities becomes the primary problem of innovation strategy. This paper utilizes Chinese university spin-offs survey data to identify the influence process from institutional innovation and organizational learning to synergistic effect of organization. Design/methodology/approach: Firstly, we found that following the procedural view, each one of these three elements can be divided into two parts. Then, we established structural equation modeling with the connections between these six subdivisions. Secondly, by taking 270 university Spin-offs in China as samples, we verified the fit of the model through statistical data on the questionnaire survey. Thirdly, we analyzed the relationship and influence path of the institutional innovation, organizational learning and synergistic effect. Findings: The results of empirical research show that institutional implementation process is positive correlation on both sides of synergistic effect, and, the intermediary role is obvious that external organizational learning played a regulatory role between institutional innovation synergistic effects. Research limitations/implications: A large-scale questionnaire survey showed that the influence path of "institutions -organization-innovation performance" are existed. Therefore, the system analysis framework should be introduced to the emergence and development of University spin-offs, and further explored the synergistic process of institutional change and organizational evolution. Practical implications: University spin-offs are a mode of university - industry cooperation, and it takes participation in market competition also as enterprise. This result of study pointed that. "Institutions" and "organizations" are the two important factors in synergistic innovation, so the synergy mechanism design should be followed by the interaction relationship between these two above. Originality/value: Synergistic innovation is the guidance theory which leads the development trend of university-industrial cooperation in China. In this paper, the "institution" and "organization", as the two primary elements, are introduced to analyze the process of synergistic innovation. Then, the authors discussed the role of the "institutional innovation" and "organizational learning" in the process of synergistic innovation, aimed at study on the operational mechanism of the influence factors.
Keywords: 650; institutional innovation; organizational learning; synergistic effect; University Spin-offs in China; SEM